The Impact of More Transparent Interfaces on Behavior in Personalized Recommendation - Schnabel, Tobias; Amershi, Saleema; Bennett, Paul; Bailey, Peter; Joachims, Thorsten (Proceedings of the International ACM SIGIR Conference on Research and Development in Information Retrieval (SIGIR), 2020)
Many interactive online systems, such as social media platforms or news sites, provide personalized experiences through recommendations or news feed customization based on people’s feedback and engagement on individual items (e.g., liking items). In this paper, we investigate how we can support a greater degree of user control in such systems by changing the way the system allows people to gauge the consequences of their feedback actions. To this end, we consider two important aspects of how the system responds to feedback actions: (i) immediacy, i.e., how quickly the system responds with an update, and (ii) visibility, i.e., whether or not changes will get highlighted. We used both an in-lab qualitative study and a large-scale crowd-sourced study to examine the impact of these factors on people’s reported preferences and observed behavioral metrics. We demonstrate that UX design which enables people to preview the impact of their actions and highlights changes results in a higher reported transparency, an overall preference for this design, and a greater selectivity in which items are liked.